The performance of licensed rotavirus vaccines and the development of a new generation of rotavirus vaccines: a review - Yuxiao Wang; Jingxin Li; Pei Liu; Fengcai Zhu (Taylor & Francis Group, 2021)
Rotavirus, which causes acute gastroenteritis and severe diarrhea, has posed a great threat to children worldwide over the last 30 y. Since no specific drugs and therapies against rotavirus are available, vaccination is considered the most effective method of decreasing the morbidity and mortality related to rotavirus-associated gastroenteritis. To date, six rotavirus vaccines have been developed and licensed by local governments. Notably, Rotarix™ and RotaTeq™ have been recommended as universal agents against rotavirus infection by the World Health Organization; however, lower efficacies were found in less-developed and developing regions with medium and high child mortality than well-developed ones with low child mortality. For now, two promising novel vaccines, Rotavac™ and RotaSiil™ were pre-qualified by the World Health Organization in 2018. Other rotavirus vaccines in the pipeline including neonatal strain (RV3-BB) and several non-replicating rotavirus vaccines with a parenteral delivery strategy are currently undergoing investigation, with the potential to improve the performance of, and eliminate the safety concerns associated with, previous live oral rotavirus vaccines. This paper reviews the important developments in rotavirus vaccines in the last 20 y and discusses problems and challenges that require investigation in the future.